Reality culture as a prevailing cultural format in Serbia - Domazet, Sanja S; Nikolić, Jelena (Sociološki pregled, 2021)
The contemporary media culture in Serbia has been marked by two trends – democratization and transformation of the media. These parallel processes on the eve of the 21st century led to the decrease in informative contents and the increase in the entertainment ones. Therefore, reality shows take primacy in Serbia, no longer being an exclusive feature of the television. This paper is aimed at researching and describing the ways in which informative contents in the Serbian media have been replaced by television reality contents, as well as the ways in which the printed media and internet portals inform about them. By the qualitative method of content analysis, this paper realizes its goal to fathom the mechanisms of the transposition of the informative content into the entertainment one, thus deconstructing journalistic practices. The results will indicate that the domestic portals relate to realities in two ways – the first and less common modality is ignoring, while the second implies uncritical acceptance of this type of content, which creates fertile soil for the development and maintenance of the so-called reality culture.